(3GdeMGSHI GdeGdjI GdeJbOeIs - (3MSjf(B, (3GdbGVjs; (3MSjf OMOhM(B, s ((3YeGf(B:s (3OGQ GdKbGaI ddfTQ hGdJhRjY(B,s, 2011)
(3GdeMGSHI Yf JhMjO GdGYeGd(B- (3EYOGO GdbhGFe GdeGdjI GdehMOI HJGQjN GdJhMjO aj Xd WQb GdeMGSHI Yf GdJhMjO(B- (3EYOGO GdbhGFe GdeGdjI HYO JGQjN JhMjO GdCYeGd(B- (3GdYedjGJ GdeJHGOdI GdeJYdbI HGdeNRhf(B- (3GdYedjGJ GdeJHGOdI GdeJYdbI HGdCUhd GdKGHJI(B- (3GdJhMjO ZjQ GdeHGTQ(B- (3eTcdGJ NGUI aj JhMjO GdCYeGd(B- (3VQjHI GdONd aj JhMjO GdGYeGds
(3GdeQGLY U(B489(3; bGFeI GdeUWdMGJ GdYdejI U(B493s
Keywords: (3GdeMGSHI(B- (3GdeGdjI GdYGeIs; (3eMGSHI GdJcGdjas